مقالات الشيخ عبد الله الغدامسي (المغربي) في صحيفتي صحابت وسودارا بجزيرة بيننج الماليزية، دراسة تحليلة : Articles of Sheikh Abdullah Al-Ghadamisi al-Maghribi in the Sahabat and Saudara Newspapers on the Malaysian Island of Penang (An Analytical study) - Adel M. Abdulaziz Al geriani; Ahmad Kamel Mohamed (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
تتناول الدراسة أحد علماء الإصلاح الليبيين في بلاد الملايو من خلال دراسة وتحليل مقالاته في صحيفتي صحابت وسودارا والتي كانا لهما دور كبير في المجتمع الملايوي أثناء مرحلة مهمة من تاريخ بلاد الملايو، وهي الفترة التي خضعت فيها لسيطرة المستعمر البريطاني الذي سعى إلى تدمير هوية الشعب ودينه وتركيبته الإجتماعية ومقوماته الأخلاقية والعرفية، ويهدف البحث إلى دراسة وتحليل مقالات الشيخ عبد الله الغدامسي المشهور بالمغربي في صحيفتي صحابت وسودارا الصادرة في جزيرة بيننج الماليزية، والتي حاول من خلالها نشر الوعي الديني والسياسي بين أبناء الشعب في الجزيرة، محارباً لجميع الفرق الضالة والمبتدعة إلى جانب إنشاء المدارس والمعاهد الدينية للجنسين متصدياً بذلك للدعاوى البريطانية الداعمة للمدارس الحديثة التي يمنع فيها تدريس المواد الدينية المتعلقة بالدين الإسلامي. لذلك فقد وجد الشيخ الغدامسي في الصحف المحلية مساحة واسعة لنشر أفكاره الإصلاحية والدعوية، والتي تقوم هذه الدراسة بعرضها وتحليلها وفق منهج علمي تحليلي يكشف أسلوب ومنهج الشيخ الغدامسي في مقالاته بصحيفتي صحابت وسودارا. الكلمات المفتاحية: مقالات، الشيخ عبد الله الغدامسي، صحيفة صحابت وسودارا، جزيرة بيننج. Abstract The current study deals with one of the Libyan reform scholars in the Malay Archipelago. It analyzes the articles of al-Ghadamisi published in the Sahabat and Saudara Newspaoers which immensely contributed to the Malay history and society during the British colonialization that sought the elimination of the Malay identity, religion and social composition of the people and their ethical and customary constituents. This research aims at investigating the articles of Sheikh Abdullah al-Ghadamisi known also as AL- Maghribi, in the Sahabat and Saudara Newspapers issued on the Malaysian island of Penang through which he tried to advocate the Islamic religion and political awareness among the people on the island. His objectives were battling all deviant and innovated practices that were alien to Islam and establishing schools and religious institutions for both genders in order to encounter the British strategy of supporting modern schools where religious subjects and Islamic studies were prohibited. Therefore, Sheikh al-Ghadamisi found in the local Newspapers an open space to publish his reformist and advocate his ideas. This study analyzes al-Ghadamisi’s works accordingly using an analytical method to uncover his scholastic approaches in his articles published in the Sahabat and Saudara Newspapers. Keywords: Articles, Sheikh Abdullah Al-Ghadamisi, Sahabat & Saudara Newspapers, Penang Island.